Inconsistencies undermine the credibility of confession evidence. (20th February 2014) - Palmer, Matthew A.; Button, Lizzie; Barnett, Emily; Brewer, Neil
Abstract : Purpose: Although inconsistencies undermine the credibility of evidence from a witness or victim, anecdotal evidence from many court cases suggests that they do not reduce the impact of confession evidence. This research provides the first empirical test of this idea by experimentally manipulating the consistency of confession evidence. Drawing on principles from attribution theory, we hypothesized that inconsistencies would undermine the credibility of confession evidence only when there was a salient, plausible alternative explanation (other than guilt) for why the defendant confessed. Methods: In two experiments (total N  =   245), participants were presented with information about a crime, including a confession statement, and asked to act as jurors in a courtroom case. As well as manipulating whether the confession was consistent or inconsistent with verifiable facts of the crime, we manipulated whether there was a salient alternative explanation for the confession: specifically, the presence of coercion ( ) or the desire to protect another suspect ( ). Results: Inconsistencies influenced participants' verdicts regardless of whether an alternative explanation was made salient, such that inconsistent confessions resulted in fewer guilty verdicts than consistent confessions. Additional mediation analysis of the data from suggested that these effects occurred, in part, because the presence of inconsistencies prompted participants to generate alternative explanations for why the defendant confessed (regardless of whether such explanations were salient in the available evidence). Conclusions: Contrary to the existing literature, these results indicate that inconsistencies can undermine the credibility of confession evidence.